Data for 3D left atrial printing acquired using open source and free software, with the aim to determine the proper size of left atrial appendage occlured. (25th November 2020) - Hecko, J; Jiravsky, O; Chovancik, J; Hudec, M; Sramko, M; Sknouril, L
Abstract: Background: The occlusion of the left atrial appendage is the treatment of choice in patients with high both thrombembolic and bleeding risks. The optimal method for size selection and occluder placement is still evolving. Based on published data, the ability to print a 3D atrial model might be helpful in these processes. Minimizing the cost of this approach may contribute to a massive extension of the methodology. Aim: To present a process of data acquisition for 3D left atrial printing without the need of using a premium software. Method: Patients indicated for percutaneous left atrial appendage closure are prepared according to standard recommendations. Afterwards, DICOM CT scans were used for our purpose. This data was transfered to the segmentation software. With the help of 3D Slicer 4.10 (slicer.org), the cardiac chambers were segmented from the contrast CT (DS CorCTA 1.0 B26f BestDiast 72%). The "Paint" function was specifically used for segmentation, marking each chambe. "GrowFromSeeds" utility was then used to automatically initialize chambers with the option of manual correction. Segments were subsequently transfered to the 3D model format (STL, 3MF). The difficulty was, that from the aforementioned contrast CT, we were only able to acquire the left atrial "cavity", not reflecting the true dimensions of the walls. Therefore, we subtracted this shape from a cuboid. Then, using function "Hollow" in 3D Builder, we gradually removed the outer part of the cuboid around the subtracted cavity, resulting in a true left atrial wall. This enabled a valid sizing of the appendage. Since this procedure was part of a blinded study, a small cuboid marker (10x10x3mm) was added to the cast for patient identification and correct 3D printing. For the printing itself, a flexible material with 30–35D hardness was used to simulate compliant cardiac tissue. Conclusion: The segmentation of the left atrium using open source and free 3D software enables to minimize printing costs which may lead to extension of this method to everyday clinical practice. Funding Acknowledgement: Type of funding source: None